БОЛАЛАРДА ТОРТИНЧОҚЛИК ҲИССИНИНГ НАМОЁН БЎЛИШИ ВА УНИНГ ОИЛА МУҲИТИ ТАЪСИРИДА КОРРЕКЦИЯЛАШ - Раззақова, Р.С.; Саидмуратова, М.Б. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of kinds of shyness positive and negative features of children‘s shyness and methods of preventing them, their correction.
Keywords: shyness; aim; situation; method; primary-school age; individual abilities; cause; correction; preventive maintenance